2017
DOI: 10.3346/jkms.2017.32.3.427
|View full text |Cite
|
Sign up to set email alerts
|

The Cut-off Values of Triglycerides and Glucose Index for Metabolic Syndrome in American and Korean Adolescents

Abstract: The aim of this study was to establish ethnic- and gender-specific cut-off values of triglycerides and glucose index (TyG index) for clinical usefulness in a representative sample of Mexican American, Non-Hispanic White, Non-Hispanic Black, and Korean adolescents. The data were collected from datasets of the National Health and Nutrition Examination Survey between 1999 and 2012, and the Korean National Health and Nutrition Examination Survey between 2005 and 2013. Receiver operating characteristic curve analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 39 publications
3
79
0
Order By: Relevance
“…Limited data are reported in pediatric age, in which the TyG index has been described as a useful predictor of metabolic abnormalities in Asian, Mexican American, Non-Hispanic White adolescents (15)(16)(17)(18)(19)(20)(21). Untill now there is no consensus for reference criteria in Caucasian children, besides no pediatric study has been conducted on this topic.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Limited data are reported in pediatric age, in which the TyG index has been described as a useful predictor of metabolic abnormalities in Asian, Mexican American, Non-Hispanic White adolescents (15)(16)(17)(18)(19)(20)(21). Untill now there is no consensus for reference criteria in Caucasian children, besides no pediatric study has been conducted on this topic.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…indicated that TyG index performed better than HOMA to estimate insulin resistance with hyperglycemic clamp in Brazilian subjects 14 . Additionally, the TyG had been demonstrated to be strongly associated with diabetes, obesity, NAFLD and even metabolic syndrome, all of which were risk factors of hypogonadism 15 18 . To the best of our knowledge, no study has investigated the application of TyG in male hypogonadism.…”
Section: Introductionmentioning
confidence: 99%
“…100 . and adolescents that do not consider pubertal status (42,43) . The lack of a consensus for cut-off points to diagnose dyslipidaemia, hypertension, hyperglycaemia and overweight status results in the adoption of country-specific references for clinical studies.…”
mentioning
confidence: 99%